Measurements of the Higgs boson production and decay rates and coupling strengths using pp collision data at √s = 7 and 8 TeV in the ATLAS experiment - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (The European physical journal. C, Particles and fields, 2016)
Combined analyses of the Higgs boson production and decay rates as well as its coupling strengths to vector bosons and fermions are presented. The combinations include the results of the analyses of the H→γγ,ZZ∗,WW∗,Zγ,bb¯,ττ and μμ decay modes, and the constraints on the associated production with a pair of top quarks and on the off-shell coupling strengths of the Higgs boson. The results are based on the LHC proton-proton collision datasets, with integrated luminosities of up to 4.7 fb−1 at s√=7 TeV and 20.3 fb−1 at s√=8 TeV, recorded by the ATLAS detector in 2011 and 2012. Combining all production modes and decay channels, the measured signal yield, normalised to the Standard Model expectation, is 1.18+0.15−0.14. The observed Higgs boson production and decay rates are interpreted in a leading-order coupling framework, exploring a wide range of benchmark coupling models both with and without assumptions on the Higgs boson width and on the Standard Model particle content in loop processes. The data are found to be compatible with the Standard Model expectations for a Higgs boson at a mass of 125.36 GeV for all models considered.
*ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A.E. Baas, O. Brandt, Y. Davygora, J.I. Djuvsland, M. Dunford, M.P. Geisler, M. Giulini, P. Hanke. J. Jongmanns, E.-E. Kluge, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, M. Wessels [und sehr viele weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 19.06.2020